Factors influencing the volatility price of bitcoin / Nur Faridza Roslan - Roslan, Nur Faridza (Faculty of Business and Management, 2020)
The purpose to conduct this study is to investigate the relationship between supply of Bitcoin, interest rate, exchange rate and oil price toward the volatility price of Bitcoin in United States. It covers the period from 1st quarter 2011 to 3rd quarter 2019, a period of 8 years. Simply, those factors are considered as influencer for volatility price of Bitcoin in United States and it has been investigated quarterly. The researcher want to investigate the factors that contribute the price of Bitcoin becomes volatile in some of period in United States. Also, the researcher want to estimate whether the independent variables have the significant or insignificant relationship toward the volatility price of Bitcoin. The researcher used secondary data in this study. In addition, the researcher also used Multiple Linear Regression to test the data collected. The researcher used this method in order to get strong result at the end of the analysis. Finally, we have come out with the conclusion and recommendation as a suggestion for a good and better decision for the price of Bitcoin in the cryptocurrency market in United States.